Wide Input Voltage Range Operation of the Series Resonant DC-DC Converter with Bridgeless Boost Rectifier - Abualkasim Bakeer; Andrii Chub; Dmitri Vinnikov; Argo Rosin (Energies, 2020)
The series resonant DC-DC converter (SRC) can regulate the input voltage in a wide range at a fixed switching frequency. In this work, the bridgeless rectifier, which is utilized intensively in the applications of the power factor correction, has been integrated into the SRC as a voltage step-up cell at the output-side of the SRC. It is shown that the conventional overlapping pulse-width modulation (PWM) of the two metal oxide semiconductor field-effect transistors MOSFETs in this rectification cell limits the input voltage regulation range of the converter due to excessive power losses in abnormal operating conditions. The abnormal operating conditions occur when the instantaneous voltage across the resonant capacitor is larger than the secondary voltage of the isolation transformer. This happens at high values of the DC voltage gain, i.e., low input voltages and high currents, which causes the resonant current to flow in the reverse direction in the same half-cycle through a parasitic path formed by overlapping PWM of the rectifier MOSFETs. The abnormal operation results in additional conduction loss in the converter as the MOSFETs of the bridgeless boost rectifier turn on at high current at the beginning of each half of the switching period. Accordingly, the overall efficiency of the converter significantly deteriorates. This paper proposes the hybrid PWM aiming to improve the efficiency of the SRC with a bridgeless boost rectifier in a wide input voltage regulation range. The converter swaps between the overlapping and the proposed short-pulse PWM schemes to drive the MOSFETs in the bridgeless boost rectifier. The transition between the two PWM schemes is defined according to the boundary condition that relies upon the operating point of the converter power and the input voltage. The proposed hybrid PWM scheme is analyzed and compared to the overlapping PWM at different levels of the input voltage and the load power. A 300 W prototype was studied in the laboratory to show the feasibility of the proposed hybrid PWM scheme with the closed-loop control system to switch between the two PWM schemes.